Power Quality Improvement by Using Statcom Control Scheme in Wind Energy Generation Interface to Grid - Sheeraz Kirmani; Brijech Kumar (Journal of Contemporary Urban Affairs, 2017)
“Electric Power Quality (EPQ) is a term that refers to maintaining the near sinusoidal waveform of power distribution bus voltages and currents at the rated magnitude and frequency.” The power quality is basically customer-centric. The increased focus on utilities toward maintaining reliable power supply by employing power quality improvement tools has reduced the power outages and blackout considerably. Good power quality is the characteristic of a reliable power supply. Low power factor, harmonic pollution, load imbalance, fast voltage variations are some common parameters which are used to define the power quality. If the power quality issues are not checked it will lead to a high electricity bill, the high running cost in industries, malfunctioning of equipment, challenges in connecting renewables. Capacitor banks, FACTS devices, harmonic filters, SVC’s, STATCOM are the solutions to achieve power quality. This paper presents the STATCOM system with the BESS and studies the impact on the power quality in a system which consists of the wind turbine generator, nonlinear load, hysteresis controller for controlling the operation of STATCOM and grid. The model is simulated in the MATLAB/Simulink. This scheme mitigates the power quality issues, improves voltage profile and also reduces harmonic distortion of the waveforms. BESS level out the imbalances caused by real power due to the intermittent nature of wind power available due to varying wind speeds.